Evaluación de la aplicación pre y pos cosecha de etileno en cebolla de bulbo (Allium Cepa L.) híbrido burguesa en la provincia de Cotopaxi 2021. - Gualan Gualan, Alicia Maribel (2021)
The emission of shoots in bulb onion represents a serious production problem since it reduces quality and yield, in addition, it is one of the main causes of post-harvest losses of onion during storage. The present investigation was carried out in two phases, one in the field in the Province of Tungurahua, Ambato Canton, Cunchibamba Parish, in the “San Jorge” neighborhood where three doses of ethylene were applied (1 cc * lt-1; 1,25 cc * lt -1; 0), in three application periods (pre-harvest, harvest without cutting stems and roots and in harvest cutting stems and roots), the second phase was carried out in the laboratory at the Experimental Center of Agricultural Sciences of the Technical University of Cotopaxi , located in the “Salache Bajo” Parish, Latacunga Canton, Cotopaxi Province where two factors were evaluated: ethylene dose and application times in a Random Complete Block Design, for the significance tests Tukey at 5% was used and it was evaluated the indicators of weight, weight variation and % of weight variation, pest incidence, diseases and physiopathies, incidence of shoots, PH, soluble solids, firmness, % of moisture and ash. The study determined that the best treatments were E1D1 and E2D1, and the best time to apply ethylene was in pre-harvest, since this helped to preserve a greater amount of physical characteristics of the bulb onion; lower weight variation (3,44) lower percentage of weight variation (0,48%), PH (5,89), greater firmness (3,60) and higher percentage of humidity (92,36%). The time of application in harvest with stems and roots reported a lower percentage in incidence of shoots (8,89%). The best dose of ethylene was 1 cc * lt-1 since it helped to prolong the useful life of the bulb onion during storage, especially it influenced the percentage of weight variation (6.28%) and the incidence of pests, diseases and physiopathies with a percentage of (2.22%).